PUBLIC RELATIONS STRATEGY APPROACH IN SHAPING POSITIVE PUBLIC PERCEPTION OF BANK SYARIAH INDONESIA'S CSR PROGRAM - Azzahwa, Inez Laydisa; Misidawati, Dwi Novaria (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Corporate Social Responsibility (CSR) has become an essential element of business strategies, including in the banking sector. Public Relations (PR) plays a crucial role in communicating CSR activities to the public and shaping positive perceptions. This research examines the approach of Public Relations at Bank Syariah Indonesia (BSI) in communicating its CSR programs and the impact of these strategies on forming a positive public perception. The study employs a qualitative descriptive approach, utilizing secondary data from literature, CSR reports, and media publications. The findings reveal that BSI’s transparent and accountable PR communication significantly enhances its public image. BSI effectively utilizes various communication channels, such as social media and mass media, to inform the public about the social impact of its CSR initiatives. The research concludes that a well-structured and responsive PR strategy plays a critical role in fostering trust and supporting the bank’s long-term social sustainability goals.Keywords: Public Relations, Corporate Social Responsibility, Positive Public Perception, Communication Strategy